The Influence Of Bank-Specific Internal Factors On Profitability In Indonesian Banking : - Maulana , Akbar; Andrian , Muhammad Ghifari; Leon , Farah Margaretha (Journal of Management, Economic, and Accounting, 2026)
This study was aims to examined the effect of specific internal factors of banks, namely bank size, capital adequacy ratio, non-performing loan ratio, liquidity ratio, dividend payout ratio, and loan ratio, on the profitability of Indonesian banks listed on the Indonesia Stock Exchange (IDX) during the period of 2012-2024. The sample consists of 8 banks with a total of 102 annual observations. The analysis method used is panel data regression with a Random Effect Model approach using Eviews 9.0 software. The results of the study show that bank size and capital adequacy ratio have a significant positive effect on profitability, while the non-performing loan ratio has a significant negative effect on profitability. Meanwhile, the liquidity ratio and dividend payout ratio are expected to have a significant effect on banking profitability. These findings have important implications for bank management in optimizing capital structure, controlling asset quality, and determining dividend policy to achieve sustainable financial performance.